Integration and Interconnection of Human Concepts in Islamic and Transpersonal Psychology - Sri Haryanto; Hendriyadi Bahtiar Daeng Sila (International Journal of Islamic Educational Psychology, 2022)
This study describes the interconnection of human conceptions in Islamic and transpersonal psychology. The research method used was qualitative with a library research model and e-journal literature that discusses humans from Islamic and transpersonal psychology perspectives. The data collection technique was through documentation. The researchers documented the literature on human and psychological e-journals and then presented them systematically. The data analysis was carried out by data reduction, data presentation, and concluding. The researchers reduced human data and Islamic psychology accessed in e-journals, then systematically presented and analyzed them descriptively-interpretatively. The results revealed that the interconnection of human concepts in Islamic and transpersonal psychology was found in the following points; (1) examining humans in the three dimensions of somatic (body), psychic (mental), and noetic (spiritual); (2) the central theme of theoretical studies; and (3) spiritual awareness (transcendental).